APLIKASI EKSTRAK KULIT BUAH NAGA SEBAGAI PEWARNA ALAMI PADA SUSU KEDELAI DAN SANTAN - Ekawati,Rostiati , Syahraeni, Prizka (AGROTEKBIS, 2015)
The study aims to find out a better concentration of dragon fruit peel extracted which capable to produce soybean and coconut milk products with stable color,  conducted in completely randomized design on two factors for chemical analysis, the first factor consisted of 3 levels dragon fruit peel extracted concentration of 20%, 30%, 40%, and the second were the product of soybean and coconut milk. The organoleptic test using a randomized block design in which the grouping was based on each panelist, the number of panelists with 15 people. Analysis parameters including color, aroma, taste, overall favorite. The results of  study showed that the better concentration of dragon fruit peel extracted was 40% that be able to produce high quality soy milk with natural color stable chemical characteristics included free fatty acid content of 0.01% and 1,15x107 cfu/ml of total microbial. Furthermore, the quality organoleptic, dragon fruit peel extract concentration of 20% were the best result that included aroma, taste and overall favorite scores were 5 (quite like), 4  (neutral) and 4 (neutral). The best concentration of dragon fruit peel extracted on soy milk the that concentration of 40% particularly  for free fatty acid  (0.69%) and total microbial (1,36x107 cfu/ml).  Futhermore, on organoleptic quality showed that the 20% concentration were the best score for aroma, flavour and overall favorite namely 5 (quite like), 4 (neutral) and 5 (quite like) respectively.